A resource inventory for the Ruamahanga Catchment, Wairarapa, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Applied Science at Massey University - Chrystall, Leila Margaret (Massey University, 2007)
Currently, there is concern around various water management issues in the Ruamahanga Catchment, Wairarapa. This concern has prompted discussion among the stakeholders of the catchment about implementing an Integrated Catchment Management (ICM) Plan in the area. A prerequist of an ICM plan is to have a detailed resource inventory that documents the current state of the catchment, the level and areas of research already carried out in the catchment, and the specific problems occurring in the catchment. This report constitutes the Resource Inventory for the Ruamahanga Catchment and will serve as a discussion document that can be used by the stakeholders to implement an ICM plan. This Inventory organises information under twelve topic headings that range from land and climate, water resources and land use, to freshwater ecology and public perceptions on the state of the water resources in the catchment. Significant issues indentified in the catchment include; deteriorating water quality in the Ruamahanga River as it flows southwards; a significant increase (~14,000 kg/year) in dissolved reactive phosphorus (DRP) loading in the Ruamahanga River segment between Te Ore Ore and Gladstone, which in most part, is a result of the Masterton Sewage Treatment Plant discharge; unsatisfactory bathing water quality at some sites on the Ruamahanga River; a lower diversity of freshwater species than the rest of the Wellington Region; current and future land use intensification which is leading to increasing demands for water; and fully allocated surface water zones and groundwater aquifers. Recommendations are provided on how to improve the quality of data in this inventory, and also on how to proceed in the future with the findings of this report in mind. Faced with similar water quality issues as the Manawatu Catchment, stakeholders of the Ruamahanga Catchment should be aware of the outcomes of Horizon Regional Council's One Plan, and observe any success and failures of the One Plan when implementing an ICM Plan in the future.
Keywords: New Zealand; Wairarapa; Natural resources surveys; Land use; Watershed management